2013
DOI: 10.1039/c3cp54045f
|View full text |Cite
|
Sign up to set email alerts
|

High current density via direct electron transfer by the halophilic anode respiring bacterium Geoalkalibacter subterraneus

Abstract: In this study the characterization of Geoalkalibacter subterraneus is presented, a novel 11 halophilic anode respiring bacteria (ARB) previously selected and identified in a 12 potentiostically controlled bioelectrochemical system (BES) inoculated with sediments from a 13 salt plant. Pure culture electroactive biofilms of Glk. subterraneus were grown during 14 chronoamperometric batch experiments at a graphite electrode poised at +200 mV (vs. SCE) 15 with 10 mM acetate as electron donor. These biofilms exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 80 publications
2
26
0
Order By: Relevance
“…The selection of Glk. subterraneus is not surprising since it is a well-known ARB (Carmona-Martínez et al, 2013;Miceli et al, 2012) and DMRB (Greene et al, 2009). This is in agreement with the expected effect of the DMRB-enrichment strategy.…”
Section: Microbial Community Analysis Of Enriched Dmrbsupporting
confidence: 86%
“…The selection of Glk. subterraneus is not surprising since it is a well-known ARB (Carmona-Martínez et al, 2013;Miceli et al, 2012) and DMRB (Greene et al, 2009). This is in agreement with the expected effect of the DMRB-enrichment strategy.…”
Section: Microbial Community Analysis Of Enriched Dmrbsupporting
confidence: 86%
“…(Bond et al, 2002), Geoalkalibacter sp. (Badalamenti et al, 2013;Carmona-Martinez et al, 2013). Phylogenetic identification using the ARB software revealed that the representative sequences of major OTUs belonging to this order were classified as Geobacteraceae related to Geobacter metallireducens (96% identity for the major OTUs of electrodes 1 and 3), a well-known electroactive bacterium (Bond et al, 2002) and as Desulfuromonadaceae related to Desulfuromonas michiganensis (93% identity for the third major OTU on electrode 2).…”
Section: Analysis Of the Microbial Communitiesmentioning
confidence: 99%
“…In BES, the electron transfer between microorganisms and bioanodes has been well elucidated for a handful of anode-respiring bacteria (ARB) such as Geobacter sulfurreducens , Rhodopseudomonas palustris (Xing et al, 2008), Thermincola ferriacetica (Parameswaran et al, 2013), Geoalkalibacter subterraneus (Carmona-Martínez et al, 2013), and Shewanella oneidensis (Marsili et al, 2008). While bacteria within the Geobacteraceae are examples of ARB using DET to transport electrons from an available electron donor (organic matter) to the solid electrode (Carmona-Martínez et al, 2013;Fricke et al, 2008), members of the Shewanellaceae have been characterized for using both DET and MET (Carmona-Martinez et al, 2011;Marsili et al, 2008). However, the Shewanellaceae produce significantly less current densities.…”
Section: Introductionmentioning
confidence: 99%